ANALISA RISIKO PILIHAN POLA TANAM =risk analysis of cropping system choice - Adi Widiyanto; Irham Irham; Slamet Hartono (Agro Ekonomi, 2002)
The research aimed to find out the risk of cropping system choice, farmers preference and affecting factors of it. Research has been done by survey in Sabrang Wetan Hamlet, Wukirsari Village, Cangkringan Sub-district, Sleman Regency to 46 farmers who implemented cropping system during October 1999 to August 2000.The risk of cropping system choice level measured by coefficient of variation stochastic dominance analysis, and efficient frontier of cropping system choice by motad programming.The result showed that the risk level order of cropping system from highest was: paddy-chilly-string bean; paddy-chilly-green bean; paddy-string bean-green bean; paddy-string bean-string bean; and paddy-paddy-paddy. Stochastic dominance analysis showed paddy-chilly-string bean as the most dominance cropping system, this result in accordance with the reality which most respondent implemented this cropping. Motad programming model showed that paddy-chilly-string bean cropping system beside contribute maximum income also has highest level of risk.